MULTIPLE INTELLIGENCE GAMES MODEL UNTUK MENGASAH KECERDASAN ANAK DI DAERAH RAWAN BENCANA JAWA TENGAH - Lilis Madyawati; Hamron Zubadi; Dede Yudi (Universitas Muhammadiyah Semarang, 2015)
The research had been done for 2 years is begun by the researcher’s desire to realize the education for all people, especially for early-aged children in disaster areas in Central Java. The education for children before disaster, during disaster, and after disaster should be considered since the children’s education must be carried out despite the disaster. The game activities, which are part of education and children’s life, are still done partially. Moreover, it doesn’t focus on multiple intelligences yet, and less attention in the children’s characteristic and necessities as well. The subjects of this research are pre-school institutions and such a thing, either formal or non formal, in five disaster areas in Central Java which include: Cilacap Regency, Banyumas Regency, Kebumen Regency, Klaten Regency, and Wonosobo Regency. After formulating the strategy of the game development model for sharpening the children’s intelligence in form of integrating and modifying all of intelligences into game activities, the researcher apply the model to the research subjects and other users of the model. Developing the initial model, trial model, revised model, evaluation, finalization, and socialization, the researcher is success to develop a model called Multiple Intelligence Games Model. The research produce some items: 1) Mapping of Multiple Intelligence Games Model implementation, 2) the implementation of Multiple Intelligence Games Model in disaster areas, 3) the potential of Multiple Intelligence Games Model implementation in disaster areas, 4) the instruction and procedure of Multiple Intelligence Games Model, and 5) textbook of educating the children using Multiple Intelligence Games Model. After the implementation of Multiple Intelligence Games Model in the children’s game activities, the children’s intelligence in disaster areas is increase.Keywords: MIGM, children’s intelligence